THE HYPOTHESIS OF WUḌŪʾ (ISLAMIC RITUAL ABLUTION) PRACTICE AS A POSSIBLE REGULATOR BETWEEN SKIN SURFACE, SKIN MICROBIOTA, AND THE OUTER WORLD - Ilir Akshija (International Islamic Medicine Forum, 2025)
Wuḍūʾ (Islamic ritual ablution) is a religious based practice performed daily by Muslims. The expanding knowledge of human skin microbiota composed of commensal and pathogenic microorganisms requires a novel approach toward their management. The importance of wuḍūʾ as a cleaning practice and skin microbiota regulator needs to be studied and applied in case results are found beneficial. A novel approach based on estimating wuḍūʾ effects at first requires a framework of dimensions pointing at possible hypotheses. A literature review will serve as a first step to identify dimensions of skin microbiota possibly affected by wuḍūʾ practice. Calculations of body areas, washing frequency and quality of used water are the following steps of the evaluation. Wuḍūʾ functions like an algorithm and a protocol. It covers 14.5% of body surface and is practiced one to five times daily. Hands are washed six times and in total are washed and rubbed twelve times from contact with other washed parts. Palm (volar) area is washed and rubbed more than opisthenar area (dorsal) part of hand. The forearm is washed thrice to the elbow and is considered a ‘grey area’ of doubtful infective potential, just one cm beyond the washed hand which can probably reinfect the already washed hand. The sequence of actions respects gravitation as a possible contaminating factor. A summary of findings shows possible dimensions wuḍūʾ can be included as a variable in a study. Wuḍūʾ practice can be of help to actual sanitization techniques. An immediate recommendation derived from the practice in times of pandemics like COVID-19 is the possible WHO (World Health Organization) recommendation of hand washing extension to elbows, as surgeons do. ABSTRAK Wuḍūʾ (wudhu) adalah praktik keagamaan yang dilakukan setiap hari oleh umat Islam. Pengetahuan yang berkembang tentang mikrobiota kulit manusia yang terdiri dari mikroorganisme komensal dan patogen membutuhkan pendekatan baru terhadap pengelolaannya. Pentingnya wuḍūʾ sebagai praktik pembersihan dan pengatur mikrobiota kulit perlu dipelajari dan diterapkan jika hasilnya terbukti bermanfaat. Pendekatan baru yang didasarkan pada estimasi efek wuḍūʾ pada awalnya membutuhkan kerangka kerja dimensi yang mengarah pada hipotesis yang mungkin. Sebuah tinjauan literatur akan berfungsi sebagai langkah pertama untuk mengidentifikasi dimensi mikrobiota kulit yang mungkin dipengaruhi oleh praktik wuḍūʾ. Perhitungan area tubuh, frekuensi pencucian dan kualitas air yang digunakan adalah langkah selanjutnya dari evaluasi. Wuḍūʾ berfungsi seperti sebuah algoritma dan protokol. Ini mencakup 14,5% dari permukaan tubuh dan dipraktikkan satu hingga lima kali sehari. Tangan dicuci enam kali dan secara total dicuci dan digosok dua belas kali dari kontak dengan bagian yang dicuci. Area telapak tangan (volar) dicuci dan digosok lebih banyak daripada area opisthenar (punggung) tangan. Lengan bawah dicuci tiga kali hingga siku dan dianggap sebagai 'area abu-abu' dengan potensi infektif yang meragukan, hanya satu cm di luar tangan yang dicuci yang mungkin dapat menginfeksi ulang tangan yang sudah dicuci. Urutan tindakan ini memperhatikan gravitasi sebagai faktor kontaminasi yang mungkin terjadi. Ringkasan temuan menunjukkan kemungkinan dimensi wuḍūʾ dapat dimasukkan sebagai variabel dalam penelitian. Praktik Wuḍūʾ dapat membantu teknik sanitasi yang sebenarnya. Rekomendasi langsung yang berasal dari praktik ini di masa pandemi seperti COVID-19 adalah kemungkinan rekomendasi WHO (Organisasi Kesehatan Dunia) untuk memperluas jangkauan cuci tangan hingga ke siku, seperti yang dilakukan para ahli bedah.